141k views
5 votes
Solve the following literal equation for x.

ax-b/c=d

User Userpal
by
5.2k points

1 Answer

1 vote

Answer:

x = (d + b/c)/a

or x = d/a + ba/c

Explanation:

1. ax - b/c = d

2. ax = d + b/c

3. x = (d + b/c)/a (can also be written as x = (d + b/c)*1/a)

4. x = d/a + ba/c

Step 1 is given.

In step 2, b/c was added to both sides of the equation. This works because division is ahead of subtraction in the order of operations.

In step 3, both sides were divided by a.

(optional) In step 4, 1/a was multiplied by the values inside the parenthesis as a means to further simplify the equation.

User Estrella
by
6.0k points